Pengaruh Pembelajaran Daring terhadap Prestasi Belajar IPS Siswa Kelas VIII SMPN 20 Bekasi - Adelia, Neneng Yulista; Putri, Eka (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2021)
Based on the research conducted by researchers at the Department of Economic Education, Panca Sakti University, Bekasi, this study aims to analyze: 1) Knowing the impact of online learning on the world of education, 2) There are limitations of learning media in online learning that affect teaching and learning, and 3) Knowing the success rate of online learning for social studies lessons at SMPN 20 Bekasi. The results of this study indicate that there is a significant influence between online learning (X) on social studies learning achievement (Y). Based on data processing and data analysis assisted by the SPSS version 16 program, a correlation coefficient (r) of 0.242 means that the influence of online learning on social studies learning achievement has a significant effect, as indicated by R Square = 0.128 which means that 12,8% of variable variation learning achievement can be affected by online learning.